The Influence of Organizational Culture on Financial Report Quality at Jakarta Water Resources Office - Dewi Kuraesin, Arlis; Suryaningsih, Maria; Darwis , Hidayat; Yunita , Anita (Manunggal Halim Jaya, 2022)
The study aims to investigate the influence of the organizational culture on the financial report quality at the Jakarta Water Resources Office. It used the quantitative method with the primary data and questionnaires. The study occurred at the Jakarta Water Resources Office from September - March 2021. It uses the questionnaire distribution. This is a causal and comparative study. The study of causality investigates the cause-and-effect relationship between the independent variable (X) and the dependent variable (Y). The population in this study is the forty-two employees of the Jakarta Water Resources office, while the sample is some of them working at the Jakarta Water Resources office. The sample uses the Slovin formulation with 5% margin error. The result of this study states the organizational culture influences the financial report quality at the Jakarta Water Resources office. Human resources became the essential factor in the financial report. Moreover, the corporate culture may affect the quality of the financial statement. The study result reveals the organizational culture positively and significantly impacts the financial report. The suggestions go to companies, financial reports, and further research. The findings suggest that a company improves the organizational culture to produce optimum quality of financial reports.